Counseling On Business Development In The Era Of Adapting To New Habits For The Group Of Household Food Industry, Margasari Sub-District Of Bandung - et. al., Verani Hartati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
During the COVID-19 pandemic, approximately 37 thousand Micro, Small, and Medium Enterprises (MSMEs) are affected due to decreased purchasing power. Since June 27, 2020, the government has started to implement the period of Adapting to New Habits (AKB or Adaptasi Kebiasaan Baru in Indonesia) for West Java. The government has allowed the opening of 90 percent of the economy in the blue zone and 60 percent in the yellow zone, hence MSMEs and economic activities can slowly come back to life. The Margasari sub-district, which is located in the Buah Batu district, Bandung City, is included in the yellow zone. This is where business actors are starting to be encouraged to actively move and be able to adapt to the AKB era. The Household Food Industry (IPRT) group is no exception, which has a quite large number in the region. The IPRT group of the Margasari sub-district does not yet have an understanding and ability in business management that can adapt to the AKB era, especially in terms of production and distribution following government recommendations.The purpose of the community service activity (PKM as Pengabdian kepada Masyarakat in Indonesia) is to serve as efforts in providing insight into managing business in the AKB era. Counseling and business strategy assistance includes knowledge in planning production, distribution and online-based marketing strategies in the AKB era.